Identification and Functional Analysis of GTP Cyclohydrolase II in Candida glabrata in Response to Nitrosative Stress - Nasuno, Ryo; Suzuki, Soma; Oiki, Sayoko; Hagiwara, Daisuke; Takagi, Hiroshi (Frontiers in Microbiology, 2022)
Reactive nitrogen species (RNS) are signal molecules involved in various biological events; however, excess levels of RNS leads to cell death and/or cellular dysfunction, called nitrosative stress. During the process of infection, pathogens are exposed to nitrosative stress induced by host-derived RNS. Therefore, the nitrosative stress tolerance mechanisms of pathogenic microorganisms are important for their infection and toxicity, and could be promising targets for antibiotics. Previously, we demonstrated that the RIB1 gene encoding GTP cyclohydrolase II (GCH2), which is the first step enzyme for the riboflavin biosynthesis pathway, is important for nitrosative stress tolerance in the yeast Saccharomyces cerevisiae. Here, we identified and characterized the RIB1 gene in the opportunistic pathogenic yeast Candida glabrata. A growth test and enzyme assay using recombinant proteins indicated that the open reading frame of CAGL0F04279g functions as RIB1 in C. glabrata (CgRIB1). Subsequently, we analyzed the effect of CgRIB1 on nitrosative stress tolerance by a growth test in the presence of RNS. Overexpression or deletion of CgRIB1 increased or decreased the nitrosative stress tolerance of C. glabrata, respectively, indicating that GCH2 confers a nitrosative stress tolerance on yeast cells. Moreover, we showed that the proliferation of C. glabrata in cultures of macrophage-like cells required the GCH2-dependent nitrosative stress tolerance mechanism. Additionally, an infection assay using silkworms as model host organisms indicated that CgRIB1 is indispensable for the virulence of C. glabrata. Our findings suggest that the GCH2-dependent nitrosative stress tolerance mechanism is a promising target for the development of novel antibiotics.